2019
DOI: 10.24293/ijcpml.v25i3.1445
|View full text |Cite
|
Sign up to set email alerts
|

The Difference Between Neutrofil Total, Neutrophil / Lymphocyte and Platelets / Lymphocyte Ratio in Normal Patients, Nstemi, Stemi

Abstract: Sindrom Koroner Akut(SKA) yaitu Non ST Elevasi Miokard Infark (NSTEMI) dan ST Elevasi Miokard Infark (STEMI) disebabkan oleh aterosklerosis pembuluh darah, merupakan proses inflamasi akut diawali kerusakan endotel. Neutrofil Absolut (NA), Neutrofil/Limfosit Ratio (NLR), Platelet/ Limfosit Ratio (PLR) merupakan petanda inflamasi sistemik pada penyakit inflamasi. Tujuan untuk membandingkan NA, NLR dan PLR sebagai petanda inflamasi pada pasien normal, NSTEMI dan STEMI . Penelitian observasional analitik dengan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the study conducted by Chawla et al 72.4%were males. 12 The mean NLR value in acute myocardial infarction was 6.175 ± 2.26.In the study conducted by Divyaprakash et al, 7 the mean NLR was 3.7±2.6 . They also concluded that an NLR of 2.34 or higher was an independent predictor of CAD.…”
Section: Discussionmentioning
confidence: 86%
“…In the study conducted by Chawla et al 72.4%were males. 12 The mean NLR value in acute myocardial infarction was 6.175 ± 2.26.In the study conducted by Divyaprakash et al, 7 the mean NLR was 3.7±2.6 . They also concluded that an NLR of 2.34 or higher was an independent predictor of CAD.…”
Section: Discussionmentioning
confidence: 86%